Implementasi Metode Certainty Factor Pada Aplikasi Sistem Pakar Untuk Upaya Mendiagnosis Penyakit Tuberkulosis Berbasis Website (Studi Kasus : UPTD Puskesmas Curug) - Septianti; Hadi Zakaria (CV. Multi Kreasi Media, 2022)
UPTD Puskesmas Curug is a community health service unit located in the Curug area, Tangerang. There are several disease clinics available at the Curug Health Center UPTD, one of which is the Tuberculosis poly. Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis and is the 10th leading cause of death in the world. In general, this disease can attack humans in the age range of 20-50 years and this disease can be transmitted directly through the air. Patients at the UPTD of the Curug Health Center have more tuberculosis than others. The number of cases of Tuberculosis is because there are still many people who do not know the early symptoms of Tuberculosis, so that Tuberculosis is getting worse and needs more special treatment. To overcome these problems, the authors conducted research to create an expert system application by applying the Certainty Factor method as a way of calculating the certainty value of a diagnosis. The application of the Certainty Factor method can strengthen the resulting diagnosis because the system has a value so that the level of certainty will be more accurate. This application aims to assist the UPTD of the Curug Health Center in diagnosing Tuberculosis as well as suggestions or solutions for prevention and treatment of the results of the diagnosis.